Proverb in Modern Linguistics: Definition, Status, Functioning - Sharipov Bobur Salimovich (Journal of Innovation in Education and Social Research, 2024)
The article discusses issues related to the study of proverbs in modern linguistics. Despite the widespread use of proverbs, this linguistic sign can be considered one of the most complex phenomena of language. Researchers note the extreme difficulty of concisely and comprehensively defining proverbs. Each of the researchers identifies different aspects in the proverb, considering them decisive. The work provides a brief overview of the most important definitions of proverbs in Russian and foreign paremiology. It is shown what basic properties of proverbs researchers put in the foreground. The minimalism of proverbs allows us to consider them a very compact container, or packaging of experience.